Behaviour, services and their future estimation towards nCOVID-19 patients in different waves of health care workers - Mahanty, Bulu; Pattanaik, Damayanti; Sarangi, Prakash Kumar (International Journal Of Community Medicine And Public Health, 2022)
Background: Health care workers (HCWs) presented frequent concerns regarding their health and their families health and high levels of psychological distress during nCOVID19 pandemic, we aimed to estimate towards the future services nCOVID-19 waves like 4th wave in India and their behavior, and services towards the nCOVID-19 Patients and whether HCWs are in more depression or anxiety level. Methods: We developed a questionnaire to study the HCWs. The questionnaire demography and data anxiety, depression behavior consists of 30 questions. Results: high-risk health care workers had elevated stress levels. We sent 200 questionnaires completed questionnaires were returned by 128 (64%) of the participants. Out of which 72 (36%) are incomplete or non-response data. Maximum age is from 30-35 male and 25-30, female age group. Highest number of male age groups from 30 to 35, 25 (37.31%), in case of female age groups from 25-30, 19 (31.15%). Overall, the number of Male 67 (52.34%) and female 61 (47.65%) of the study. From the above descriptive statistics gives that overall average age of female with standard deviation (29.98±6.38), and with overall male, average and standard deviation (32.27±6.60). Median age of female is 27 and Male is 30 years of age. By using the linear regression analysis, we predict the future behaviors and services for upcoming pandemic is very less anxiety and depression with (p<0.001) significant. Conclusions: In conclusion, our study highlights that HCWs are both female and male are predicted less depression and anxiety about the behavior and future pandemic services.